EMIRS Observations of the Aphelion‐Season Mars Atmosphere - Michael D. Smith; Khalid Badri; Samuel A. Atwood; Christopher S. Edwards; Philip R. Christensen; Michael J. Wolff; Tanguy Bertrand; François Forget; Eman Al Tunaiji; Christopher Wolfe; Nathan Smith; Saadat Anwar (Geophysical Research Letters)
Abstract Thermal infrared spectra taken by the Emirates Mars Infrared Spectrometer (EMIRS) on‐board the Emirates Mars Mission (EMM) spacecraft are well suited for the retrieval of surface temperatures, the atmospheric temperature profile from the surface to ∼40 km, and the column abundance of dust aerosols, water ice clouds, and water vapor. A constrained linear inversion retrieval routine that includes multiple scattering has been developed and optimized for this purpose. Here, we present a brief overview of the retrieval algorithm and first atmospheric science results from observations taken by EMIRS over the first Earth year of EMM Science Phase operations. These retrievals show extensive water ice clouds, typical for the aphelion season of these observations, and the expected north polar summer maximum and subsequent equatorward transport of water vapor is well documented. An unusually strong and early regional dust storm and its associated thermal response were also observed.